Paclitaxel Enhances the Innate Immunity by Promoting NLRP3 Inflammasome Activation in Macrophages - Zeng, Qiong-zhen; Yang, Fan; Li, Chen-guang; Xu, Li-hui; He, Xian-hui; Mai, Feng-yi; Zeng, Chen-ying; Zhang, Cheng-cheng; Zha, Qing-bing; Ouyang, Dong-yun (Frontiers in Immunology, 2019)
Microtubules play critical roles in regulating the activation of NLRP3 inflammasome and microtubule-destabilizing agents such as colchicine have been shown to suppress the activation of this inflammasome. However, it remains largely unknown whether paclitaxel, a microtubule-stabilizing agent being used in cancer therapy, has any influences on NLRP3 inflammasome activation. Here we showed that paclitaxel pre-treatment greatly enhanced ATP- or nigericin-induced NLRP3 inflammasome activation as indicated by increased release of cleaved caspase-1 and mature IL-1β, enhanced formation of ASC speck, and increased gasdermin D cleavage and pyroptosis. Paclitaxel time- and dose-dependently induced α-tubulin acetylation in LPS-primed murine and human macrophages and further increased ATP- or nigericin-induced α-tubulin acetylation. Such increased α-tubulin acetylation was significantly suppressed either by resveratrol or NAD+ (coenzyme required for deacetylase activity of SIRT2), or by genetic knockdown of MEC-17 (gene encoding α-tubulin acetyltransferase 1). Concurrently, the paclitaxel-mediated enhancement of NLRP3 inflammasome activation was significantly suppressed by resveratrol, NAD+, or MEC-17 knockdown, indicating the involvement of paclitaxel-induced α-tubulin acetylation in the augmentation of NLRP3 inflammasome activation. Similar to paclitaxel, epothilone B that is another microtubule-stabilizing agent also induced α-tubulin acetylation and increased NLRP3 inflammasome activation in macrophages in response to ATP treatment. Consistent with the in vitro results, intraperitoneal administration of paclitaxel significantly increased serum IL-1β levels, reduced bacterial burden, dampened infiltration of inflammatory cells in the liver, and improved animal survival in a mouse model of bacterial infection. Collectively, our data indicate that paclitaxel potentiated NLRP3 inflammasome activation by inducing α-tubulin acetylation and thereby conferred enhanced antibacterial innate responses, suggesting its potential application against pathogenic infections beyond its use as a chemotherapeutic agent.